(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The study included the isolation and diagnosis of the fungi from the door of the laboratories (microbology ,technical biology )in the technical institute of Babylon from the medical department. The study appeared many of the different kinds of fungi: Absidia sp,Candidia sp, Aspergillus sp,Penicillum sp. The rate of appearance of the type of the fungi in microbology laboratory is the higher than the technical biology laboratory other.The rate of appearance of the fungi Aspergillus niger was 36.8% and Absidia ,Penicililum was 21.05% , Candida sp was 15.7 % , Aspergillus flavus 5.2% while in the technical biology the fungi Aspergillus terrus was 15.7% and the fungi Penicililum sp,Candida albcans, Apergillus niger was 20% , Absidia sp ,Alternaria sp was 10%.The study showed the influence of the heating water extract hot watering extract the race track in the concentration which is used( 10,20,30, 40) mg /ml on some of fungi. The rate of reduction is appeared 100% of the fungi Candida albicans in the concentration (30,40) mg/ml and the range of the diameter colony of the yeast Candida albicans in the concentration 30 mg/ml the (1)sanatamtar. While the fungi Aspergillus niger in the concentration (10,20)mg/ml is not given any resistance toward the extract.